Perbandingan Metode SAW dan Topsis pada Sistem Pendukung Keputusan Seleksi Penerima Beasiswa - Wahyuni Eka Sari; Muslimin B; Selvia Rani (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
SMK TI LABBAIKA provides scholarships every semester to students who meet the requirements. The selection process still uses the manual method based on the Headmaster's knowledge. The suitable decision support systems and methods are needed to minimize errors in decision making and get fair decision results. In this study, two decision support system methods were chosen, namely Simple Additive Weighting (SAW) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The SAW and TOPSIS methods were chosen because they have simple calculations. A comparison of the two methods is carried out to determine the best method for selecting scholarships. The criteria used in this study are student status, number of family members, parent's occupation, parent's income, and semester grades. The 20 alternative data is used for testing. Based on the results of testing the accuracy for the SAW method is 45% while for TOPSIS is 60%.